2013
DOI: 10.2217/fvl.13.18
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Pandemics of 1918 and 2009: A Comparative Account

Abstract: The 2009 influenza pandemic A(H1N1)pdm09 of swine origin and the continued circulation of highly pathogenic avian H5N1 strain in humans are stark reminders of the unpredictable nature of the influenza virus. Experiences from the 1918 and 20th century influenza pandemics helped immensely in the preparation of a better response for A(H1N1)pdm09. The explosive pattern of the 1918 pandemic makes it a benchmark for pandemic planning and preparedness today. Its similarities with the 2009 pandemic makes it even more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Based on risk factor analysis, age group 15-24 years old has higher risk to be infected by H1N1pdm09. This finding is consistent with the previous study that has been conducted in 11 states where 75% of confirmed cases of influenza H1N1pdm09 infection were at age <30 years with a peak at 10-19 years of age [9].…”
Section: Discussionsupporting
confidence: 93%
“…Based on risk factor analysis, age group 15-24 years old has higher risk to be infected by H1N1pdm09. This finding is consistent with the previous study that has been conducted in 11 states where 75% of confirmed cases of influenza H1N1pdm09 infection were at age <30 years with a peak at 10-19 years of age [9].…”
Section: Discussionsupporting
confidence: 93%
“…Both influenza A and B viruses are known to cause annual epidemics and a strict surveillance program throughout the world is in action to monitor the slightest changes in their genome due to genetic drift or shift. IAV has also been associated with several pandemics in the past however, the IBV and ICV has never been the cause of any pandemic scenario owing to their limitation of host range and less frequent mutations reported till date [4,6,9]. The surveillance activities related to ICVs have not gained much importance compared to IAVs and IBVs as it has been associated with mild clinical conditions.…”
Section: Origin Epidemiology and Pathogenesis Of Influenza D Virusmentioning
confidence: 99%
“…They are enveloped viruses with segmented genome, comprising of single stranded negative sense RNA. Influenza viruses cause acute respiratory illness and of the four known types, the influenza A virus is a significant public health concern with highest rates of morbidity and fatality [4,5,6]. They have a wide host range (Figure 1) and often jumps the species barrier [7].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal influenza viruses are one of the foremost public health concerns, especially influenza type A viruses that have been associated with the annual epidemics worldwide [33]. The recent 2009 H1N1 pandemic caused high morbidity [34,35] and mortality [36,37,38], and was a reminder that influenza viruses are highly unpredictable [3,39,40,41] and continuous efforts are needed to manage pandemic scenarios in short time. Antiviral drugs that are currently approved to treat influenza include the Adamantanes (M2 ion-channel protein inhibitors) and the neuraminidase inhibitors such as zanamivir and oseltamivir [42].…”
Section: Nucleic Acid-based Therapeuticsmentioning
confidence: 99%